2018
DOI: 10.1111/1756-185x.13286
|View full text |Cite
|
Sign up to set email alerts
|

Radiology and biomarkers in assessing disease activity in Takayasu arteritis

Abstract: Takayasu arteritis (TA) is a rare and chronic large-vessel vasculitis that predominantly affects aorta and its main branches. It occurs mainly in females <40 years. Precise assessment of disease activity is one of the major difficulties in the long-term management of TA. Until now, the accuracy of traditional activity index is still controversial. During these years, due to rapid development of radiological technology and researches of pathogenesis, new measurements and biomarkers have been applied to monitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Type V and type IV are unequivocally the most frequently reported angiographic involvement patterns in previously published studies regarding childhood‐onset Takayasu arteritis . Similar to other case series, in our study the most common type of involvement pattern was type IV followed by type V with respect to Numano's angiographic classification.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Type V and type IV are unequivocally the most frequently reported angiographic involvement patterns in previously published studies regarding childhood‐onset Takayasu arteritis . Similar to other case series, in our study the most common type of involvement pattern was type IV followed by type V with respect to Numano's angiographic classification.…”
Section: Discussionsupporting
confidence: 88%
“…Childhood‐onset Takayasu arteritis is reported to be a more refractory disease with lower rates of remissions compared to adult counterparts . Assessment of disease activity and treatment response is still the most difficult challenge for clinicians . There are limited data on clinical features, assessment of disease activity and long‐term outcome of Takayasu arteritis in children.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal analysis demonstrated that a significant increase in sIL-6R levels was only apparent at baseline (47). Consequently, sIL-6R is suggested to mirror disease activity in TA (48). Additional research on cytokines and chemokines in TA showed that serum/plasma levels of IL-8, and chemokine (C-C motif) ligands (CCL) 2 and (CCL) 5, cytokines which guide immune cells to the site of inflammation by means of chemotaxis, were increased in TA patients in comparison with healthy controls, and were also elevated when comparing individuals with active TA to those in remission.…”
Section: Large Vessel Vasculitismentioning
confidence: 99%
“…The concentration of PTX-3 but not that of CRP was, according to Tombetti et al, significantly increased in TA patients who suffered from worsening arterial lesions detected by conventional and computed tomography (CT) angiography. Consequently, plasma PTX-3 levels could serve as a surrogate parameter of disease activity in arteries (48, 52, 54, 55). The reasons for an increase in PTX-3 in TA are similar to those mentioned in the context of GCA.…”
Section: Large Vessel Vasculitismentioning
confidence: 99%
“…However, the geographical differences, association with different major histocompatibility complex classes and differential treatment responses to same biological agents suggest that these may not be same. Then there is a detailed write‐up by Jiang's group on the role of radiology and biomarkers in assessing disease activity in TAK . The precise assessment of TAK disease activity has been a challenge in clinical practice.…”
mentioning
confidence: 99%